The Australian Curriculum: Mathematics - World Class for Déjà Vu - Atweh, Bill; Miller, Donna; Thornton, Steve (Mathematics Education Research Group of Australasia, 2012)
This chapter raises two questions about the Australian Curriculum: Mathematics: What practices it may inspire and what might be its contributions to the national goals of education. The first questions is about the internal cohesiveness, or the synergy between the curriculum’s stated aims and rationale, on the one hand, and the content and its articulation on the other, and what vision of mathematics education they may inspire across the different jurisdictions which would adopt it. The second question is about its external cohesiveness, or the synergy between the curriculum itself and the national expectations of education and what contribution it may make to the public good in the Australian society. The chapter questions whether only lip service in the elaborations is given to the General Capabilities, Cross-curricular Priorities, and the high order Proficiencies. Similarly, the lack of focus on conceptualisation and articulation of the purposes of learning mathematics opens up the possibilities of designing school-based curricula that are far from achieving the national goals of active and informed citizens.